2020
DOI: 10.34209/equ.v22i2.1326
|View full text |Cite
|
Sign up to set email alerts
|

Audit Committee Characteristics and Financial Performance: Indonesian Evidence

Abstract: This research investigates the effect of audit committee characteristics, which includes independence (ACIN), size (ACSIZE), competence (ACCO), and frequency of meetings (ACMT) on the financial performance (PERF) of manufacturing firms listed on the Indonesian Stock Exchange for the year of 2016 and 2017. PERF is measured and proxy with the return on assets (ROA); ACIN is measured by the percentage of members from outside the company; ACCO is measured using percentage of audit committee members who have accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 31 publications
3
15
0
4
Order By: Relevance
“…This because financial statements have to be reviewed by an audit committee before they are disclosed to the public (Ashari, 2020). This result is in line with research conducted by Yuliani (2018), where in the research it was found that the characteristics of the audit committee together simultaneously influenced the financial performance of pharmaceutical companies listed on the Indonesia Stock Exchange in 2012-2016.…”
Section: Simultaneously Test (T Test)supporting
confidence: 84%
See 3 more Smart Citations
“…This because financial statements have to be reviewed by an audit committee before they are disclosed to the public (Ashari, 2020). This result is in line with research conducted by Yuliani (2018), where in the research it was found that the characteristics of the audit committee together simultaneously influenced the financial performance of pharmaceutical companies listed on the Indonesia Stock Exchange in 2012-2016.…”
Section: Simultaneously Test (T Test)supporting
confidence: 84%
“…This is reinforced by the results of research Zraiq (2018), which states that the audit committee size is positive and significant associated with EPS. Also in Ashari and Krismiaji research in 2020 study showed that the size of the audit committee has a positive effect on company performance (Ashari, 2020). H1: The size of the audit committee middle category affected the company performance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 92%
See 2 more Smart Citations
“…;Ashari & Krismiaji (2020);Alderman & Jollineau (2020); andWidiatami et al (2020) concluded that the development of audit committees has a strong positive effect on auditor independence. This indicates that in existence of audit committee in has constructive influence on auditor's independence.Information Technology: the result of this study shows that information technology with coefficient of regression [=0.263] has positive and statistically insignificant since (p-value of 0.…”
mentioning
confidence: 99%